Peran Konseling Keluarga Dalam Memperbaiki Hubugan Orang Tua dan Anak di Lingkungan Keluarga - Nst, Nasta Fauzia Adhani (CV. Pusdikra Mitra Jaya, 2024)
This research aims to explain research findings regarding the role of parents in instilling character values ??in children and the way families and people behave in educating children. Apart from that, this method can help families improve the relationship between parents and children in the family environment. This research is qualitative research that uses descriptive analysis to determine the role of counseling in improving parent-child relationships in the family environment. Research results are summarized based on research focus. According to research, the first is the cause of family conflict between parents and children, the second is the family counseling process, the first research is the cause of family conflict between parents and children, the second is the family counseling process which can identify basic problems in the relationship between parents and children, third namely the counseling approach most commonly used to improve the relationship between parents and children and finally the family counseling process which can help improve communication between parents and children.